2019
DOI: 10.1002/lary.27763
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative quality‐of‐life measures predict acute postoperative pain in endoscopic sinus surgery

Abstract: Objectives Recent increases in opioid‐related mortality have prompted a critical evaluation of postoperative pain management across all specialties. However, successfully limiting narcotic overprescription requires perioperative identification of patients who are at risk for high postoperative pain. Unfortunately, quality data to guide practice patterns are lacking. We therefore prospectively investigated several possible predictive factors of postoperative pain after endoscopic sinus surgery (ESS). Methods Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In our results, the proportion of nasal polyposis patients was not significantly different between GERD vs non-GERD group, in consistence with literature before 18 . Chowdhury et al reported pre-operative QOL as a prognostic factor for post-operative outcomes in CRS patients 19 . Pre-operative SNOT-22 was associated with post-operative improvement of CRS-related QOL in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In our results, the proportion of nasal polyposis patients was not significantly different between GERD vs non-GERD group, in consistence with literature before 18 . Chowdhury et al reported pre-operative QOL as a prognostic factor for post-operative outcomes in CRS patients 19 . Pre-operative SNOT-22 was associated with post-operative improvement of CRS-related QOL in our study.…”
Section: Discussionmentioning
confidence: 99%
“…One study encompassing 64 patients undergoing ESS identified a modified Lothrop as an independent significant predictor of postoperative day 3 pain. 53 However, in another retrospective review of 121 patients, septoplasty, revision, Draf IIB, and Draf III procedures were not associated with additional opioid prescriptions. 55 Consequently, it remains unclear whether extent of surgery has any impact on postoperative pain or opioid use.…”
Section: Needs Assessmentmentioning
confidence: 96%
“…Studies demonstrating associations between increased analgesic needs and preoperative health status, comorbid depression, and worse baseline quality-of-life assessment scores will need to be substantiated in larger populations while simultaneously developing strategies to effectively manage patients identified as being at risk. 19,21,53,54 Development of predictive metrics to identify an individual's preoperative predisposition to experience persistence of acute postoperative pain as chronic postsurgical pain are needed to better characterize this unique population with an increased likelihood to develop opioid dependence. 52 Similarly, there is limited literature that offers guidance on how to manage patients with previous substance abuse, where indicators for consistent involvement of a chronic pain team may be warranted.…”
Section: Needs Assessmentmentioning
confidence: 99%
“…Neither extent of surgery nor disease severity influenced VAS or MED in either cohort, 25 and there was no effect of SNOT-22 on these outcomes. 26 Both these results require confirmation with larger sample sizes and uniform surgical technique. The average patient in the control group required 1.6 tablets of oxycodone on POD 1 to 2 and <1 tablet for the remainder of the postoperative course.…”
Section: Discussionmentioning
confidence: 97%